The Vark Learning Styles among University Students of Business Schools - Espinoza-Poves, Jenny L. (2019)
The aim of this research was to know the learning styles in the students of the business schools of a private university in the Department of Lambayeque. An applied survey, a test of VARK learning styles, was applied to 218 university students (71 students of Administration and 147 students of International Business Administration), from the II to X term of the business schools of said University. During the first semester of the 2018, it was found that 25.5% of students have a multimodal learning style. It was also found that age is significantly associated with learning styles. Finally, a significant relationship between the learning style and the professional school is demonstrated. On the one hand the Administration students have mostly a multimodal learning style (two or more styles), while international business students have a reading/writing learning style.